2019
DOI: 10.1177/1468797619873109
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing and relating user engagement in festivals’ virtual brand communities: An analysis of Sónar’s Twitter and Facebook

Abstract: Festival branding is undergoing a revolution based on the consolidation of new communicative behaviours in virtual brand communities (VBCs), above all, channelled through social media platforms. Although the literature on festivals has analysed engagement in VBCs, this study provides an in-depth observation of the profiles of festival VBCs users, how they modulate engagement attributes and behaviours and how these relate to their engagement focus, highlighting festival branding while also considering other mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Festivals now take place in both physical and virtual spaces, and virtual platforms play a major role in the emergence of communities connected through festival activities. These online communities, non-geographically bound and based on virtual interactions allow for a wider engagement with festivals, their communities “on-site” and their destinations (Garay and Morales, 2020). Online, digital cultural and artistic activities have the potential of wider engagement and promotion, since they can be appreciated even from afar, giving the possibility to extend the typical audience of a festival or event.…”
Section: Discussionmentioning
confidence: 99%
“…Festivals now take place in both physical and virtual spaces, and virtual platforms play a major role in the emergence of communities connected through festival activities. These online communities, non-geographically bound and based on virtual interactions allow for a wider engagement with festivals, their communities “on-site” and their destinations (Garay and Morales, 2020). Online, digital cultural and artistic activities have the potential of wider engagement and promotion, since they can be appreciated even from afar, giving the possibility to extend the typical audience of a festival or event.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the importance of social media in marketing, there is limited research that explores its impacts on and relationships with event attendees (Hudson et al , 2015). Beyond its marketing functions, it is evident that social media have evolved from being a source of information (Laurell and Björner, 2018) to platforms that enhance involvement, co-create narratives (Garay and Morales, 2020) and improve place-brand engagement (Laurell and Björner, 2018). Social media encourage consumers to share experiences among themselves, and facilitate attendees' engagement (Robertson et al , 2015) by providing a liminal space to mediate consumer experiences (Van Winkle and Bueddefeld, 2020).…”
Section: Technological Innovations and Events: The State Of The Artmentioning
confidence: 99%
“…Laurell and Björner (2018) found a high correlation between the engagement of festival goers, the festival itself and its associated place at the 8 M Festival 2015 (Sweden). Garay and Morales (2019), using the Sonar Music Festival in Spain as a case study, explored virtual brand communities on Twitter and Facebook with more than 2,150 posts. Danielsen and Kjus (2019), using data from Twitter and Wimp music streaming services in Norway, found that the appearance of a musician at a festival that had been discussed on SM correlated with the number of musicians being listened to through streaming services (Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%